Idiopathic Brain Herniation: A Report of Two Paediatric Cases. Issue 5 (October 2014) - Koc, Gonca; Doganay, Selim; Bayram, Ayse Kacar; Gorkem, Sureyya Burcu; Dogan, Mehmet Sait; Per, Huseyin; Coskun, Abdulhakim
'Idiopathic' herniation of the brain is a rare entity previously reported in 13 cases. It may be incidentally encountered in neuroimaging studies acquired for various clinical indications. We herein describe two cases of idiopathic brain herniation that were incidentally diagnosed. A 12-year-old boy presented with a six-month history of daytime sleepiness and sudden spells of sleep. Herniation of the left inferior temporal gyrus was revealed in MRI acquired with the suspicion of epilepsy. His overnight polysomnogram and multiple sleep latency tests were compatible with the diagnosis of narcolepsy. The other case, a two-year-old girl, was transferred from an outside hospital due to partial seizures with the fever. Herniation of the precuneal gyrus was encountered in MRI acquired after controlling her seizures with the initiation of phenytoin. The brain herniations of both patients were considered to be inconsistent with their medical conditions, so that they were symptom-free with only medical treatment for following three and six months, respectively. This is a rare presentation of idiopathic brain herniation as an incidental finding that accompanied narcolepsy and epilepsy. Awareness of this entity would avoid excessive surgical and medical treatments.